Iodine deficiency and real-life supplementation ineffectiveness in Polish pregnant women and its impact on thyroid metabolism - Filipowicz, Dorota; Szczepanek-Parulska, Ewelina; Mikulska-Sauermann, Aniceta A.; Karaźniewicz-Łada, Marta; Główka, Franciszek K.; Szymanowski, Krzysztof; Ołtarzewski, Mariusz; Schomburg, Lutz; Ruchała, Marek (Frontiers in Endocrinology, 2023)
Introduction Iodine is a pivotal component of thyroid hormones, and its deficiency leads to negative pregnancy outcomes. Therefore, during gestation, additional iodine supplementation is recommended. Objectives By evaluating a group of women from western Poland, the study updated on iodine status during pregnancy and the effectiveness of iodine supplementation in relation to the maternal and neonatal thyroid function. Patients and methods A total of 91 women were recruited before the delivery between 2019 and 2021. During the medical interview, the patients declared their dietary supplements intake. Thyroid parameters (TSH, ft3, ft4, a-TPO, a-Tg, and TRAb) were measured in the serum of mothers and in the cord blood of newborns after birth. Urinary iodine concentration (UIC) and urine/creatinine (UIC/crea) ratio were assessed in single urine samples using a validated high-performance liquid chromatography with ultraviolet detection (HPLC-UV). Neonatal TSH screening from dried blood spot was analyzed. Results Pregnant women showed a median (interquartile range) UIC of 106 (69–156) µg/liter and UIC/crea ratio of 104 (62–221) µg/g, whereas approximately 20% had UIC/crea below 50 µg/g, indicating iodine deficiency. The iodine supplementation ratio was 68%. No significant differences in UIC, UIC/crea and thyroid parameters were found between iodine supplemented and non-supplemented groups; however, the highest ioduria was detected when iodine was supplemented in addition to levothyroxine in comparison with both substances administered separately. Patients with UIC/crea within 150–249 µg/g demonstrated the lowest TSH and a-TPO levels. Screening TSH was above 5 mIU/liter in 6% of children. Conclusions Despite the national salt iodization and the recommendation to supplement iodine during gestation, the status of the abovementioned microelement and real-life intake revealed the ineffectiveness of the current iodine-deficiency prophylaxis model in pregnancy.